MENGUNGKAP SEJARAH DAN MOTIF BATIK SEMARANGAN - Yuliati, Dewi (Paramita: Historical Studies Journal, 2010)
Batik Semarang was born in line with the needs of the people of Hyderabad of the material with a new motif or style tailored to the taste, intention, and creativity of the craftsmen. Batik is a combination of several countries influence developing in Indonesian culture. Based on its shape, Batik designs can be divided into two major groups, namely geometric and non-Geometric. The development of Semarangan batik was due to the fact that certain motif of batik can only be worn by certain people, not for all group of people. Batik semarangan craftments are found in coastal regions. It displays the design composing of ornaments plucked from marine environment. Indonesian Batik develops not only to display a blending of court Batik designs with the coastal Batik technique, but also to incorporate other ornaments which come from many various ethnic groups in Indonesia. Ã‚Â  Key words: batik, history, ornaments, marine environment, designs Ã‚Â  Batik Semarang lahirkan sejalan dengan kebutuhan dari orang-orang dari Hyderabad akan bahan dengan motif atau gaya baru yang berdasarkan pada rasa, niat, dan kreatifitas dari pembuatnya. Batik merupakan perpaduan dari pengaruh beberapa negara yang berkembang dalam budaya Indonesia. Ditinjau dari desainnya, desain batik dapat dibagi menjadi dua kelompok utama, yakni geometrik dan nongeometrik. Pengembangan yang dilakukan terhadap batik semarangan disebabkan adanya beberapa motif batik yang hanya digunakan oleh kalangan tertentu, dan tidak boleh untuk kalangan umum. Pengrajin batik Semarangan berkembang di kawasan pesisir. Ia menampilkan desain yang terdiri atas berbagai ornamen yang menunjukkan ciri khas kemaritiman. Batik ini dikembangakan tidak hanya menampilkan desain batik khas pesisiran, tetapi juga memasukkan berbagai ornament dari beragam kelompok etnis di Indonesia. Ã‚Â  Kata kunci: batik, sejarah, ragam hias, lingkungan pesisir, desain Ã‚Â